Peran Studi Kelayakan Bisnis Dalam Peningkatan UMKM (Studi Kasus UMKM di Kabupaten Kudus) - Gunawan, Karebet (Universitas Islam Negeri Sunan Kudus, 2018)
Kudus Regency is one of the districts in Central Java whose economic activities that are dominated by the industrial sector both in large industries such as the Djarum and Pura Barutama, and small industries. The industrial sector is the main pillar of the economy of Kudus with a contribution about 63.55 percent. The research approach used in this study is a qualitative approach, where the author does not use statistical data in collecting and identifying data. Qualitative methods are best used to develop theories that are built from data obtained through the field. Operational Management is a function or management activity that includes planning, organization, staffing, coordination, direction and supervision of the company's operations. There are three main problems faced by the company such as the problem of determining the company position, design, and other operational problems. Determination of the company position in the community aims to have the company in accordance with community needs, and can be run economically, effectively and efficiently. The similarities between theory and practice, for example, share market segmentation so that in determining what items will be sold or produced according to market needs so that the segments will be targeted or the segments to be targeted, the position of goods will also be determined. While differences in practice in determining production or sales do not use calculations such as through sales forecasts and targets to be achieved.